TREATMENT OF ENDOMETRIOSIS: AN UMBRELLA REVIEW OF SYSTEMATIC REVIEWS AND META-ANALYSES WITH ASSESSMENT OF EVIDENCE OVERLAP - Wojciech Żywiec; Alicja Dorota; Michał Dorota; Kacper Karaban; Nicole Maryniak; Jakub Rzeszutek (International Journal of Innovative Technologies in Social Science, 2026)
Background: Endometriosis is a chronic inflammatory disease associated with pain, infertility, and impaired quality of life. Numerous systematic reviews and meta-analyses have evaluated available treatments but overlapping evidence and methodological heterogeneity limit interpretability.Objective: To synthesize secondary evidence on endometriosis management using an umbrella review with explicit assessment of evidence overlap.Methods: Systematic reviews with quantitative meta-analyses published between 2019 and 2026 were identified through PubMed. Methodological quality was assessed using AMSTAR 2. Evidence was synthesized narratively across therapeutic domains and overlap of primary studies was quantified using the Corrected Covered Area (CCA).Results: Forty-nine systematic reviews were included. Overall, methodological quality was moderate to high. Evidence overlap was generally low but high in selected domains, particularly hormonal pretreatment before assisted reproductive technologies. Progestins and gonadotropin-releasing hormone modulators consistently reduce endometriosis-related pain. Surgical excision of ovarian endometriomas reduced recurrence but impaired ovarian reserve, while postoperative hormonal suppression reduced recurrence risk.Conclusions: This umbrella review supports selected hormonal and surgical strategies for endometriosis management while highlighting evidence redundancy and key knowledge gaps.